Professional development and applied ethics - Arenas, Chester Dave G. (Manila, Philippines : Edric Publishing House, 2021)
Every chapter of the book describes the skills, knowledge and performance outcomes required to develop the ability of students to become professionals in their field by understanding of improving one's personality and ways on how they are going to be valued in the business industry by means of presenting their ideas.
UNIT 1. Personality Development -- UNIT 2. Intellectual Development -- UNIT 3. Social development -- UNIT 4. Emotional development -- UNIT 5. Physical development -- UNIT 6. Moral and spiritual -- UNIT 7. Career Development.
Includes bibliographical references.
Keywords: CAREER DEVELOPMENT